(untitled) (Comprehensive Journal of Science, 2026)
Choosing a university major is one of the most important fateful decisions facing students during their transition to it. The choice of major is not limited to the student’s abilities and personal inclinations only, but is greatly influenced by multiple factors. The study aimed to reveal the family roles in guiding children toward choosing a university major. The study sample consisted of 68 female individuals from the Faculty of Education, Janzur. These results indicate that the parents’ level of education has a great motivation in choosing the scientific major for their children. Also, the Libyan family participates in choosing the major based on its previous experiences. The family does not only support before the choice, but continues to follow up on academic performance and provide continuous support, which reflects the specificity of the family role in Libyan society.